The Effectiveness Of Problem Based Learning Model In Increasing Historical Learning Outcomes - Johan Pattiasina; *Jems Sopacua (Universitas Syiah Kuala, 2022)
This Learning is essentially a process of interaction between students and their environment, resulting in changes in behavior for the better. The results of observations that have been made at SMA Negeri 10 Ambon in history subjects, it is known that cognitive learning outcomes in students are still low, ie almost 80% of students get scores below 60. One of the learning models that is able to train students in overcoming problems This is done by applying the Problem Based Learning (PBL) model. This study aims to analyze the effect of the use of the PBL learning model on the learning outcomes of history at SMA Negeri 10 Ambon and to analyze the effectiveness of the use of the PBL learning model in improving the learning outcomes of history at SMA Negeri 10 Ambon. This type of research is a pure experiment using a pretest-posttest group design. The samples in this study were students in class X-B as the experimental class and class X-C as the comparison class. The results of data analysis in this study concluded that: (1) the PBL learning model affected the learning outcomes of history at SMA Negeri 10 Ambon; and (2) the PBL learning model is effective in improving history learning outcomes at SMA Negeri 10 Ambon.